La Princesse d'Elide and Les Amants magnifiques -- A Critical Analysis and Defence - Scott, David (My University, 1967)
A detailed external and internal examination of La Princesse d'Elide and Les Amants magnifiques, considering the two plays as an integral and essential part of Moliere's work and attempting to rescue them from the oblivion into which they have so unjustly fallen.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures